Vietnam 1946 : how the war began - Tønnesson, Stein (From Indochina to Vietnam, 2010)
Stein Tønnesson explores the antecedents of the Vietnam War back to 1946 when at the end of the world war, French administrators returned to their protectorates in South East Asia, & found themselves challenged by a new political nationalism that drew inspiration from the Russian & Chinese revolutions.